Have Sentiments Influenced Malaysia's Stock Market Volatility During the 2008 Crisis? - Yacob, Nathrah (Journal of Reviews on Global Economics, 2019)
This paper examined the effects of both macro-economic and investor sentiment on the volatility of the Malaysian stock market, during the 2008 global financial crisis. However, as the measurement for investor sentiment is unavailable, we constructed an investor sentiment composite index from a number of proxies, namely; the stock market turnover, number of Initial public offerings (IPO) and its initial returns, advance decline ratio, and consumer sentiment index by employing a strict process of Factor analysis with Principal component analysis' extraction. By employing Autoregressive Distributive Lags (ARDL) model, we observed the failure of macroeconomic fundamentals to significantly predict the Malaysian stock market's volatility during the crisis period while investor sentiment was a significant factor that influenced the market. These findings support the notion that investors tend to behave irrationally during crisis periods and these may assist practitioners in formulating specific investment strategies during crucial periods in order to gain abnormal returns.